Intimations of Immortality in the Thought of Jesus: The Ingersoll Lecture for 1959 - Cadbury, Henry Joel (Harvard theological review, 1960)
The historic Ingersoll lectureship on the Immortality of Man requires of the lecturer both some legitimate extension of its terms and some necessary limitation of his field. One is justified in supposing that the pious layman who planned the foundation was not thinking in highly technical terms, but like laymen of our day was thinking of a widely shared belief in the post mortem survival or revival of those who die. If he had wished to specify the indiscriminate persistence of the individual as a philosophical tenet of the nature of man, he could well have used the more familiar term — the immortality of the soul. On the other hand, if he had wished to be faithful to the wording of much of the Bible and to the Church's creeds, he would have spoken of the Resurrection of the Dead.